Characterization of a Multigene Family Undergoing High-Frequency DNA Rearrangements and Coding for Abundant Variable Surface Proteins in Mycoplasma agalactiae - Glew, M. D. (American Society for Microbiology, 2000)
A family of abundant surface proteins (Vpmas [variable proteins of Mycoplasma agalactiae]) undergoing phase variation in M. agalactiae has been characterized using monoclonal antibodies and specific polyclonal sera. Two expressed members of 39 kDa (Vpma39) and 34 kDa (Vpma34), which varied in expression between clones of a lineage, shared a common amino-terminal sequence but were immunologically distinct. An amino-terminal oligonucleotide probe identified multiple vpma genes which were clustered within a 14-kb ClaI genomic fragment. Rearrangements were found to have occurred within the vpma locus between clones which correlated with changes in their Vpma phenotype. Two neighboring vpma genes were cloned and sequenced from one M. agalactiae clonal variant expressing Vpma39. The two genes, vpmaX and vpmaY, were orientated divergently and shared highly homologous 5′ untranslated regions, 25-amino-acid (aa) lipoprotein leader sequences, and amino-terminal sequences. The vpmaY gene coded for 346 aa and 84% of the open reading frame, comprised of 1.5 units of a large repeat of 186 aa. Although the sequence for an entire second vpmaY repeat was present, it was prematurely terminated by insertion of two nucleotides. The vpmaX gene encoded 221 aa and possessed 102 aa of the 186-aa repeat of vpmaY. Many of the features in common between the vpma genes were also found to be shared by the vsp genes of M. bovis, which also undergo DNA rearrangements concomitant with phenotypic changes. Since M. bovis is the closest phylogenetic relative to M. agalactiae, the vpma and vsp gene families most probably represent homologous systems.